Sei scritti in cerca di autore: il Corpus Caspari - DeSpirito, Giuseppe (Augustinianum, 2022)
The main aim of this study is to provide some new considerations to support the contested thesis that the Corpus Caspari has to be understood as a unified set of texts drawn up by a single author. Both theological and biographical considerations allow the safe identification of the composer of this ensemble with the future Sixtus III (432-440). Moreover, all the projects that the pontiff carried out, from Santa Maria Maggiore to the monastery he founded in the vicinity of the catacombs, testify to the same opinions on asceticism, virginity and material goods as are expressed in the six letters. Even the signature of some of those letters-treaties should be evaluated as authentic, and it can be connected only to Sixtus III.